Advertisements
Advertisements
Question
`1+((tan^2 theta) cot theta)/(cosec^2 theta) = tan theta`
Solution
LHS = `((1+ tan^2 theta) cot theta)/ (cosec^2 theta) `
=` (sec^2 theta cot theta)/(cosec^2 theta )`
=`(1/cos^2thetaxxcos theta/sin theta)/(1/sin^2 theta)`
=`1/(cos theta sin theta) xx sin^2 theta`
=`sintheta/costheta`
=` tan theta`
=RHS
Hence, LHS = RHS
APPEARS IN
RELATED QUESTIONS
Prove the following trigonometric identities.
`(cos A cosec A - sin A sec A)/(cos A + sin A) = cosec A - sec A`
Prove the following trigonometric identities
sec4 A(1 − sin4 A) − 2 tan2 A = 1
Prove that `(sec theta - 1)/(sec theta + 1) = ((sin theta)/(1 + cos theta))^2`
Prove the following identities:
cosec4 A (1 – cos4 A) – 2 cot2 A = 1
(i)` (1-cos^2 theta )cosec^2theta = 1`
`cosec theta (1+costheta)(cosectheta - cot theta )=1`
`tan theta /((1 - cot theta )) + cot theta /((1 - tan theta)) = (1+ sec theta cosec theta)`
`(1-tan^2 theta)/(cot^2-1) = tan^2 theta`
`(1+ cos theta - sin^2 theta )/(sin theta (1+ cos theta))= cot theta`
If `(cosec theta - sin theta )= a^3 and (sec theta - cos theta ) = b^3 , " prove that " a^2 b^2 ( a^2+ b^2 ) =1`
Four alternative answers for the following question are given. Choose the correct alternative and write its alphabet:
sin θ × cosec θ = ______
If `x/(a cosθ) = y/(b sinθ) "and" (ax)/cosθ - (by)/sinθ = a^2 - b^2 , "prove that" x^2/a^2 + y^2/b^2 = 1`
Prove that :(sinθ+cosecθ)2+(cosθ+ secθ)2 = 7 + tan2 θ+cot2 θ.
Prove that: sin6θ + cos6θ = 1 - 3sin2θ cos2θ.
Choose the correct alternative:
sin θ = `1/2`, then θ = ?
Prove that `sintheta/(sectheta+ 1) +sintheta/(sectheta - 1)` = 2 cot θ
Prove that `sqrt(sec^2 theta + "cosec"^2 theta) = tan theta + cot theta`
Show that tan4θ + tan2θ = sec4θ – sec2θ.
Show that, cotθ + tanθ = cosecθ × secθ
Solution :
L.H.S. = cotθ + tanθ
= `cosθ/sinθ + sinθ/cosθ`
= `(square + square)/(sinθ xx cosθ)`
= `1/(sinθ xx cosθ)` ............... `square`
= `1/sinθ xx 1/square`
= cosecθ × secθ
L.H.S. = R.H.S
∴ cotθ + tanθ = cosecθ × secθ